Obesity in Patient with Grown Up Congenital Heart Disease (GUCH) Ventricular Septal Defect (VSD) with Pulmonary Hypertension in Sanglah Hospital, Bali - Natasya N., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Obesity in Patient with Grown Up Congenital Heart Disease (GUCH) Ventricular Septal Defect (VSD) with Pulmonary Hypertension in Sanglah Hospital, Bali